Spatiotemporal evolution and influencing factors of coordinated development between cultivated land use eco-efficiency and new-type urbanization: insights from Henan Province, China - Liu, Chenyang (Frontiers in Environmental Science, 2025)
China confronts challenges of inefficient cultivated land utilization and ecological pressures amid rapid urbanization. Coordinated development of cultivated land use eco-efficiency (CLUEE) and new-type urbanization (NTU) is essential for high-quality growth. As a rapidly urbanizing major grain-producing province, Henan is confronted with a serious imbalance in the development of CLUEE and NTU.Existing research lacks comprehensive spatiotemporal analysis of their coupling coordination relationship at fine scales, limiting precise policy formulation. This study quantifies CLUEE and NTU dynamics in Henan using integrated super-SBM and entropy-weighted models, elucidates coupling coordination mechanisms, and proposes spatially differentiated governance strategies. Key findings demonstrate that: (1) The CLUEE in Henan Province rose significantly from 0.09 in 2002 to 0.47 in 2022. At the county scale, there is a transition from point-like diffusion centered on Zhengzhou to continuous expansion, and low-efficiency clusters persist in the western mountainous areas. The overall NTU rose from 0.15 to 0.32, spatially, it presents high-value corridors along the traffic axis and a gradient descent zone centered on Zhengzhou. (2) Overall, the coupling coordination degree has increased from 0.31 to 0.59. At the municipal scale, Hebi leads the province, while Shangqiu is slightly out of balance. The high-value areas in counties are spreading from single-core to T-shaped corridors. (3) The driving factors show temporal and spatial heterogeneity: County-level disposable income dominates globally, while local fiscal budgets and the degree of terrain roughness shape regional interactions. The inhibitory effects on per capita cultivated land area and fiscal revenue have intensified. Agricultural mechanization has shifted from inhibition to promotion, highlighting the path differentiation between intensive development in northeast region and ecological constraints in southwest region of Henan Province. These findings reveal that the co-evolution of CLUEE and NTU in Henan Province operates through a complex synergy of resources, technology, and policy, characterized by spatially heterogeneous, non-linear interactions among multiple factors. This study underscores the significance of the county-level research, which enables local governments to implement more targeted policy regulation.